Frequency octupling radio over fiber system with multiple remote antenna units - Hussein, A. H.; Yaakob, S.; Anas, S. B. A.; Mahmood, Rawa Muayad; Abdul Kadir, Muhammad Zamzuri; Mahmud, Azwan (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Bidirectional radio over fiber (RoF) transmission to multiple remote antenna units (RAUs) with frequency octupling is proposed in this paper. The proposed RoF system uses a dual-port Mach-Zehnder modulator (DP-MZM) and an arrayed waveguide grating (AWG) to generate millimeter-wave (mm-wave) to four different RAUs. Bit Error Rate (BER) and received optical power are key parameters used to measure the performance of the system. From the simulation results, it is shown that the proposed system achieves an acceptable performance a fiber distance of 50 km with a BER of 10-12. Furthermore, the results indicate that the dispersion-induced power penalties for both uplink and downlink transmission of all RAUs are less than 1 dB. In summary, the proposed system simplifies the RoF system by reusing wavelengths and utilizing low RoF frequency through the frequency-octupling technique.